2021
DOI: 10.3390/s21062127
|View full text |Cite
|
Sign up to set email alerts
|

INTEGRATION Large-Scale Modeling Framework of Direct Cellular Vehicle-to-All (C-V2X) Applications

Abstract: The transportation system has evolved into a complex cyber-physical system with the introduction of wireless communication and the emergence of connected travelers and connected automated vehicles. Such applications create an urgent need to develop high-fidelity transportation modeling tools that capture the mutual interaction of the communication and transportation systems. This paper addresses this need by developing a high-fidelity, large-scale dynamic and integrated traffic and direct cellullar vehicle-to-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…However, the system was developed for small scale networks and does not scale well with large road networks. In [6], the authors developed a novel analytical model for the Dedicated Short Range Communication (DSRC) communication technology and incorporated it within a microscopic traffic simulator, the INTEGRATION software [2], to enable modeling of communication and traffic mobility in large-scale transportation systems. In [3], the authors utilized the analytical model for the DSRC communication technology to conduct their sensitivity analysis of both the DSRC communication system and the penetration ratio of connected vehicles and their impacts on the eco-routing application on a city-wide large scale road network.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the system was developed for small scale networks and does not scale well with large road networks. In [6], the authors developed a novel analytical model for the Dedicated Short Range Communication (DSRC) communication technology and incorporated it within a microscopic traffic simulator, the INTEGRATION software [2], to enable modeling of communication and traffic mobility in large-scale transportation systems. In [3], the authors utilized the analytical model for the DSRC communication technology to conduct their sensitivity analysis of both the DSRC communication system and the penetration ratio of connected vehicles and their impacts on the eco-routing application on a city-wide large scale road network.…”
Section: Related Workmentioning
confidence: 99%
“…In this section we describe the logic of the C-EEDR application in the context of the INTEGRATION [2], since we used it in our simulations for evaluation. The INTEGRATION software is an agent-based microscopic traffic assignment and simulation software.…”
Section: Energy-efficient Dynamic Routing Using Ideal Communicationmentioning
confidence: 99%
“…The vehicle storage data structure representation is not described. The authors in [ 21 ] propose a large-scale traffic modeling solution that is based on INTEGRATION traffic simulator where the vehicle positions are stored, updated and queried using Grid Cells data structure with update index. Their query operation is linear with the number of vehicles on the road network and the update operation is constant.…”
Section: Related Workmentioning
confidence: 99%
“…Route planning algorithms use and impact different aspects (e.g., traffic information) of daily travel experience as is presented and evaluated in various works [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. From implementation cost perspective, it was shown that traffic modeling through simulation is an efficient and reliable approach [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Considering all the above mentioned challenges and achievements, we found that there is an urgent need to develop a scalable traffic modeling database that can be used by navigation systems to predict and avoid congestion based on accurate traffic information during route planning.…”
Section: Introductionmentioning
confidence: 99%
“…The authors again used the INTEGRATION traffic simulator and an analytical model to implement the communication features of C-V2X and coupled them together in one execution environment. They scaled up the running time by leveraging a spatial index to accelerate the computation time of the communication model and tested it on the downtown Los Angeles network, modeling a total of approximately 145,000 vehicles[65]. In TableVI, we summarize the various parameters associated with the different simulator studies.…”
mentioning
confidence: 99%